Negative electrode material and preparation method and application thereof
By loading copper into the porous carbon structure of biomass, a sodium ion battery negative electrode material with superior performance was prepared, which solved the problems of limited sodium storage capacity and short cycle life of existing materials, and achieved high energy density and long life battery performance.
Patent Information
- Application Number
- CN202311416951.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing sodium ion battery negative electrode materials have limited sodium storage capacity, limited cycle life, and low energy density, making it difficult to meet the needs of high energy density and long life.
By loading copper into the porous carbon structure of biomass, the negative electrode material is prepared by immersion, spray drying and high-temperature reduction methods, thereby improving its electrical conductivity and energy storage capacity.
It significantly improves the first week of Coulomb efficiency, charging specific capacity and circulation capacity retention rate of sodium ion batteries, extends the cycle life of the battery, and improves the stability and safety of the battery.
Smart Images

Figure CN119905537A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of renewable energy and the increasing demand for energy storage, battery technology has been at the forefront of continuous improvement and innovation. As a potential energy storage device, sodium-ion batteries have attracted the interest of a wide range of researchers. Compared with traditional lithium-ion batteries, sodium-ion batteries have more extensive material resources.
[0003] The negative electrode material of the battery plays a key role in the battery performance. Traditional battery negative electrode materials are usually carbon materials, such as natural graphite or amorphous carbon, which perform well in some aspects, but also have some limitations. These limitations include: limited sodium storage capacity, which makes it difficult to meet the needs of high energy density; during long-term cycle charge and discharge, carbon negative electrode materials are prone to expansion and contraction, resulting in limited cycle life of the battery; the energy density of sodium-ion batteries is still low and needs to be improved to meet the needs of various applications. Therefore, seeking new and better-performing battery negative electrode materials has always been a key challenge in the research field. Summary of the invention
[0004] The purpose of the present invention is to provide a negative electrode material and a preparation method and application thereof in view of the defects existing in the prior art. The preparation method can load copper into a biomass porous carbon structure, so that the prepared negative electrode material has the advantages of both biomass porous carbon and copper, and can improve the electrochemical properties of sodium ion batteries such as the first-week coulomb efficiency, charge specific capacity and cycle capacity retention rate.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a negative electrode material, the preparation method comprising:
[0006] dissolving a copper salt in deionized water to obtain a copper precursor solution;
[0007] Immersing the biomass porous carbon in the copper precursor solution while stirring to obtain a mixed solution; wherein the mass ratio of the biomass porous carbon to the copper element in the copper salt is 20:1-200:1; the stirring time is 1 hour-10 hours, and the stirring rate is 500 rpm-2000 rpm;
[0008] The mixed solution is spray-dried to obtain a powdery substance mixed with copper salt and biomass polycarbon;
[0009] Under an inert atmosphere, the powdered material is placed in a rotary kiln for sintering, so that the copper salt in the powdered material is decomposed and reduced by carbon to copper element, which is loaded into the biomass porous carbon to obtain the negative electrode material.
[0010] Preferably, the copper salt includes one or more of copper sulfate, copper nitrate or basic copper chloride.
[0011] Preferably, the mass ratio of copper ions to solvent in the copper precursor solution is 1:2000-1:10.
[0012] Preferably, the biomass porous carbon includes one or more of wood porous carbon, coconut shell porous carbon or straw porous carbon.
[0013] Preferably, the air inlet temperature of the spray drying is 150°C-250°C, the air outlet temperature is 110°C-150°C, and the frequency is 150Hz-280Hz.
[0014] Preferably, the sintering is specifically:
[0015] The temperature is raised from room temperature to 600°C-1000°C at a heating rate of 2°C / min-10°C / min, and kept at this temperature for 2 hours-10 hours.
[0016] Preferably, the inert atmosphere is nitrogen or argon.
[0017] In a second aspect, the present invention provides a negative electrode material, which is prepared by any preparation method described in the first aspect.
[0018] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material described in the second aspect.
[0019] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the third aspect.
[0020] The present invention provides a method for preparing a negative electrode material, wherein copper ions are loaded onto biomass porous carbon by impregnation and spray drying, and then the metal copper ions are reduced to metal copper by high-temperature reduction, thereby obtaining a negative electrode material. The negative electrode material utilizes the high surface area, electrical conductivity and adjustable structure of the biomass porous carbon material and the good electrochemical properties of copper, and can improve the electrochemical performance of the negative electrode material of the sodium ion battery, thereby improving the electrochemical performance of the sodium ion battery such as the first-week coulomb efficiency, charge specific capacity and cycle capacity retention rate, and can also improve the stability of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A flow chart of a method for preparing a negative electrode material provided by an embodiment of the present invention;
[0022] Figure 2 This is a SEM image of the coconut shell porous carbon-supported copper negative electrode material prepared in Example 1 of the present invention;
[0023] Figure 3 This is one of the EDS images of the coconut shell porous carbon-supported copper negative electrode material prepared in Example 1 of the present invention;
[0024] Figure 4 This is the second EDS image of the coconut shell porous carbon-loaded copper negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0027] The present invention provides a method for preparing a negative electrode material, the process of which is as follows: Figure 1 As shown, the following steps are included:
[0028] Step 110, dissolving a copper salt in deionized water to obtain a copper precursor solution;
[0029] Specifically, to accelerate the dissolution rate of the copper salt, the solution can be stirred for a certain period of time by a dispersing machine. The mass ratio of copper ions to solvent in the copper precursor solution is 1:2000-1:10, preferably 1:1000-1:500. The copper salt can specifically include one or more of copper sulfate, copper nitrate or basic copper chloride.
[0030] Step 120, immersing the biomass porous carbon in a copper precursor solution while stirring to obtain a mixed solution;
[0031] Wherein, in this step, copper ions can be loaded into the structure of biomass porous carbon. Biomass porous carbon can specifically include one or more of wood porous carbon, coconut shell porous carbon or straw porous carbon. The mass ratio of biomass porous carbon to copper element in copper salt is 20:1-200:1. The stirring time is 1 hour to 10 hours, and the stirring rate is 500 rpm to 2000 rpm.
[0032] Step 130, spray drying the mixed solution to obtain a powdery substance mixed with copper salt and biomass multi-carbon;
[0033] Specifically, the spray drying can be performed in a spray drying apparatus. The air inlet temperature of the spray drying can be 150° C.-250° C., the air outlet temperature can be 110° C.-150° C., and the frequency can be 150 Hz-280 Hz.
[0034] Step 140, under an inert atmosphere, the powdered material is placed in a rotary kiln for sintering, so that the copper salt in the powdered material is decomposed and reduced by carbon to copper element, which is loaded into the biomass porous carbon to obtain a negative electrode material.
[0035] Specifically, the inert atmosphere is nitrogen or argon. The rotary kiln can be heated at a heating rate of 2°C / min-10°C / min, so that the rotary kiln is heated from room temperature to 600°C-1000°C, and kept at the above temperature for 2 hours-10 hours. The negative electrode material is a biomass porous carbon-loaded copper negative electrode material.
[0036] The following are the chemical reaction equations for the thermal decomposition of several copper salts and their reduction to copper:
[0037] CuSO4=CuO+SO3↑;
[0038] 2Cu(NO3)2=2CuO+4NO2↑+O2↑;
[0039] 2Cu2(OH)3Cl=4CuO+2HCl+2H2O;
[0040] 2CuO+CΔ2Cu+CO2↑.
[0041] The prepared negative electrode material has the following advantages:
[0042] 1. Improve conductivity: Copper is a good conductive material, and loading copper on porous carbon can significantly improve the conductivity of the material. This is very important for negative electrode materials because high conductivity helps improve battery performance and efficiency.
[0043] 2. Increase battery capacity: The copper loading can provide additional active materials, increasing the energy storage capacity of the battery. This is very beneficial for improving the energy density and battery performance of the battery.
[0044] 3. Improve battery cycle life: Copper loading can slow down the capacity decay of the material and improve the battery cycle life, which means the battery can maintain high performance for a longer time.
[0045] 4. Increase the diffusion rate of sodium ions: The porous carbon structure can provide more sodium ion diffusion channels, and the copper loading can further promote the diffusion of sodium ions in the material, thereby increasing the charging and discharging speed of the battery.
[0046] 5. Reduce material expansion: The copper loading helps to reduce the volume change of the porous carbon material, reduce the expansion and contraction of the battery during charging and discharging, and contribute to the stability of the battery.
[0047] 6. Improve battery safety: Copper loading can improve battery stability and reduce the risk of battery under high current and high temperature environment.
[0048] In summary, the preparation method of a negative electrode material provided in an embodiment of the present invention loads copper ions onto biomass porous carbon by impregnation and spray drying, and then uses a high-temperature reduction method to reduce the metal copper ions to metal copper elemental substance to obtain a negative electrode material. The negative electrode material utilizes the high surface area, conductivity and adjustable structure of the biomass porous carbon material and the good electrochemical properties of copper, which can improve the electrochemical performance of the negative electrode material of the sodium ion battery, thereby improving the electrochemical performance of the sodium ion battery such as the first week coulomb efficiency, charge specific capacity and cycle capacity retention rate, and can also improve the stability of the sodium ion battery.
[0049] The negative electrode material provided by the embodiment of the present invention can be applied to the electrode material of sodium ion batteries.
[0050] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing the negative electrode material using the method provided by the above embodiment of the present invention, as well as the electrochemical properties of the prepared negative electrode material.
[0051] Example 1
[0052] In the first step, 0.502 kg of copper sulfate was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper sulfate precursor solution.
[0053] In the second step, 20 kg of coconut shell porous carbon was weighed and added into the copper sulfate precursor solution. The solution was immersed for 2 hours while stirring at a rate of 500 rpm to obtain a mixed solution.
[0054] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper sulfate and coconut shell porous carbon. The spray drying frequency is 150 Hz, the air inlet temperature is 240°C, and the air outlet temperature is 150°C.
[0055] In the fourth step, under a nitrogen atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 5°C / min so that the temperature of the rotary kiln rises from room temperature to 800°C, and is kept at 800°C for 2 hours to decompose the copper sulfate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into coconut shell porous carbon to obtain coconut shell porous carbon loaded copper negative electrode material.
[0056] The prepared coconut shell porous carbon-loaded copper negative electrode material was used as the negative electrode material of the sodium ion battery, and a button-type sodium ion half-cell was assembled for testing. The specific process is as follows:
[0057] First, 15 g of the total material of coconut shell porous carbon-loaded copper negative electrode material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) was weighed in a mass ratio of 90%:5%:5%. 0.75g of PVDF was added to 24.25g of N-methylpyrrolidone (NMP) and placed in a disperser at a speed of 2000r / min to obtain a dispersed and clear glue solution; 0.75g of SP was added to the glue solution and dispersed again at 2000r / min for 40min to obtain a slurry; 13.5g of coconut shell porous carbon-loaded copper negative electrode material was added to the slurry, dispersed at 2000r / min for 40min, and then an appropriate amount of NMP was added to adjust the viscosity to 2000mPa.s to obtain a negative electrode slurry; the negative electrode slurry was sieved with a 180-mesh screen and then coated on a copper foil; the coated electrode was dried in an oven at 110°C for 5 hours; after drying, it was cut into a circular negative electrode electrode with a diameter of 8mm. Under vacuum conditions, the electrode was dried at 120°C for another 6 hours and then transferred to a glove box for standby use.
[0058] Then, the button-type sodium ion half-cell was assembled in a glove box with an argon atmosphere using the above-mentioned negative electrode sheet. The electrolyte of the assembled button-type half-cell was 1 mol / L sodium hexafluorophosphate (NaPF6), and the solvent of the electrolyte was ethylene carbonate (EC) and diethyl carbonate (DEC), wherein the volume ratio of EC to DEC was 1:1. The counter electrode was metallic sodium.
[0059] Finally, electrochemical tests were conducted to evaluate its electrochemical performance. The test procedure was: pre-standing for 8 hours; then rate discharge (0.1C, 0V), rate discharge (0.02C, 0V), standing for 5 minutes; rate charge (0.1C, 2V), standing for 5 minutes; test the charge specific capacity and first cycle efficiency, and then test the cycle capacity retention rate of 100, 200, 300, and 500 cycles.
[0060] Example 2
[0061] In the first step, 2.51 kg of copper sulfate was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper sulfate precursor solution.
[0062] In the second step, 20 kg of coconut shell porous carbon was weighed and added into the copper sulfate precursor solution. The solution was immersed for 2 hours while stirring at a rate of 500 rpm to obtain a mixed solution.
[0063] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper sulfate and coconut shell porous carbon. The spray drying frequency is 150 Hz, the air inlet temperature is 240°C, and the air outlet temperature is 150°C.
[0064] In the fourth step, under a nitrogen atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 5°C / min so that the temperature of the rotary kiln rises from room temperature to 800°C, and is kept at 800°C for 2 hours to decompose the copper sulfate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into coconut shell porous carbon to obtain coconut shell porous carbon loaded copper negative electrode material.
[0065] Afterwards, the prepared coconut shell porous carbon-loaded copper negative electrode material was used as the negative electrode material of the sodium ion battery, and a button-type sodium ion half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0066] Example 3
[0067] In the first step, 0.502 kg of copper sulfate was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper sulfate precursor solution.
[0068] In the second step, 20 kg of coconut shell porous carbon was weighed and added into the copper sulfate precursor solution. The solution was immersed for 5 hours while stirring at a rate of 500 rpm to obtain a mixed solution.
[0069] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper sulfate and coconut shell porous carbon. The spray drying frequency is 150 Hz, the air inlet temperature is 240°C, and the air outlet temperature is 150°C.
[0070] In the fourth step, under a nitrogen atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 5°C / min so that the temperature of the rotary kiln rises from room temperature to 800°C, and is kept at 800°C for 2 hours to decompose the copper sulfate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into coconut shell porous carbon to obtain coconut shell porous carbon loaded copper negative electrode material.
[0071] Afterwards, the prepared coconut shell porous carbon-loaded copper negative electrode material was used as the negative electrode material of the sodium ion battery, and a button-type sodium ion half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0072] Example 4
[0073] In the first step, 0.502 kg of copper sulfate was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper sulfate precursor solution.
[0074] In the second step, 20 kg of coconut shell porous carbon was weighed and added into the copper sulfate precursor solution, and then immersed for 10 hours at a rate of 500 rpm while stirring to obtain a mixed solution.
[0075] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper sulfate and coconut shell porous carbon. The spray drying frequency is 150 Hz, the air inlet temperature is 240°C, and the air outlet temperature is 150°C.
[0076] In the fourth step, under a nitrogen atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 5°C / min so that the temperature of the rotary kiln rises from room temperature to 800°C, and is kept at 800°C for 2 hours to decompose the copper sulfate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into coconut shell porous carbon to obtain coconut shell porous carbon loaded copper negative electrode material.
[0077] Afterwards, the prepared coconut shell porous carbon-loaded copper negative electrode material was used as the negative electrode material of the sodium ion battery, and a button-type sodium ion half-cell was assembled for testing. The specific assembly and testing process was the same as in Example 1.
[0078] Comparative Example 1
[0079] In this comparative example, coconut shell porous carbon is directly used as the negative electrode material of the sodium ion battery to assemble and test the button-type sodium ion half-cell, wherein the specific assembly and testing process is the same as that of Example 1.
[0080] Table 1 is the EDS element content test data in Examples 1-4. Table 2 is the electrochemical performance test data of button-type sodium ion half cells assembled in Examples 1-4 and Comparative Example 1.
[0081] serial number Carbon content (percentage) Copper content (percentage) Example 1 99.8% 0.2% Example 2 97% 3.1% Example 3 99.4% 0.6% Example 4 99.1% 0.9%
[0082] Table 1
[0083]
[0084] Table 2
[0085] As can be seen from Table 1, due to the different addition amounts of copper sulfate in Example 1 and Example 2, the ratio of copper ions to solvent in the copper precursor solution is different. The ratio of copper ions to solvent in Example 1 is 1:500, and in Example 2 it is 1:100. Therefore, it can be concluded that increasing the copper ion concentration can increase the loading amount of copper element in coconut shell porous carbon. Compared with Example 3 and 4, Example 1 only prolongs the immersion time. It can be concluded that as the immersion time is extended, the loading amount of copper element in coconut shell porous carbon can also be increased.
[0086] As can be seen from Table 2, the first week coulombic efficiency, charge specific capacity and cycle capacity retention rate of Examples 1-4 are better than those of Comparative Example 1. This is because the coconut shell porous carbon prepared in the embodiment of the present invention is loaded with copper. The loading of copper makes the coconut shell porous carbon loaded with copper negative electrode material prepared in this application have the advantages of porous carbon and copper. For example, the structure of porous carbon can provide more sodium ion diffusion channels, and the loading of copper can further improve the conductivity of porous carbon, increase the energy storage capacity of the battery, improve the cycle life of the battery, reduce the expansion of the material, and improve the safety of the battery. In short, the loading of copper has many advantages for the negative electrode material of sodium ion batteries, such as improving battery performance, cycle life and safety.
[0087] Combination Figure 2-4 As shown, it can be seen that copper is relatively evenly loaded in the coconut shell porous carbon.
[0088] Example 5
[0089] In the first step, 1.456 kg of copper nitrate was weighed, poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper nitrate precursor solution.
[0090] In the second step, 10 kg of wood porous carbon was weighed and added into the copper nitrate precursor solution, and then immersed for 8 hours with stirring at a rate of 1000 rpm to obtain a mixed solution.
[0091] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper nitrate and wood porous carbon. The spray drying frequency is 280 Hz, the air inlet temperature is 150°C, and the air outlet temperature is 110°C.
[0092] In the fourth step, under an argon atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 2°C / min so that the temperature of the rotary kiln rises from room temperature to 600°C, and is kept at 600°C for 8 hours to decompose the copper nitrate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into wood porous carbon to obtain wood porous carbon-loaded copper negative electrode material.
[0093] Example 6
[0094] In the first step, 0.6 kg of copper nitrate was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a copper nitrate precursor solution.
[0095] In the second step, 10 kg of wood porous carbon was weighed and added into the copper nitrate precursor solution, and then immersed for 4 hours at a rate of 1500 rpm while stirring to obtain a mixed solution.
[0096] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with copper nitrate and wood porous carbon. The spray drying frequency is 200 Hz, the air inlet temperature is 250°C, and the air outlet temperature is 130°C.
[0097] In the fourth step, under an argon atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 10°C / min so that the temperature of the rotary kiln rises from room temperature to 1000°C, and is kept at 1000°C for 3 hours to decompose the copper nitrate to obtain copper oxide, which is then reduced by carbon to copper element and loaded into wood porous carbon to obtain wood porous carbon loaded copper negative electrode material.
[0098] Example 7
[0099] In the first step, 0.2 kg of basic copper chloride was weighed and poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a basic copper chloride precursor solution.
[0100] In the second step, 20 kg of straw porous carbon was weighed and added into the basic copper chloride precursor solution, and immersed for 1 hour while stirring at a speed of 2000 rpm to obtain a mixed solution.
[0101] In the third step, the mixed solution is input into a spray dryer for spray drying to obtain a powdery substance mixed with basic copper chloride and straw porous carbon. The spray drying frequency is 230 Hz, the air inlet temperature is 200°C, and the air outlet temperature is 120°C.
[0102] In the fourth step, under an argon atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 5°C / min so that the temperature of the rotary kiln rises from room temperature to 700°C, and is kept at 700°C for 10 hours to decompose basic copper chloride to obtain copper oxide, which is then reduced by carbon to single copper and loaded into straw porous carbon to obtain straw porous carbon-loaded copper negative electrode material.
[0103] Example 8
[0104] In the first step, 1 kg of basic copper chloride is weighed, poured into 100 kg of deionized water in batches, and stirred for 2 hours at a speed of 1500 rpm by a disperser to obtain a basic copper chloride precursor solution.
[0105] In the second step, 10 kg of straw porous carbon was weighed and added into the basic copper chloride precursor solution, and immersed for 6 hours with stirring at a rate of 2000 rpm to obtain a mixed solution.
[0106] The third step is to input the mixed solution into a spray dryer for spray drying to obtain a powdery substance mixed with basic copper chloride and straw porous carbon. The spray drying frequency is 180 Hz, the air inlet temperature is 230°C, and the air outlet temperature is 125°C.
[0107] In the fourth step, under an argon atmosphere, the powdered material is placed in a rotary kiln for sintering, and the rotary kiln is heated at a heating rate of 9°C / min so that the temperature of the rotary kiln rises from room temperature to 900°C, and is kept at 900°C for 5 hours to decompose basic copper chloride to obtain copper oxide, which is then reduced to copper element by carbon and loaded into straw porous carbon to obtain straw porous carbon-loaded copper negative electrode material.
[0108] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The preparation method comprises: dissolving a copper salt in deionized water to obtain a copper precursor solution; Immersing the biomass porous carbon in the copper precursor solution while stirring to obtain a mixed solution; wherein the mass ratio of the biomass porous carbon to the copper element in the copper salt is 20:1-200:1; the stirring time is 1 hour-10 hours, and the stirring rate is 500 rpm-2000 rpm; The mixed solution is spray-dried to obtain a powdery substance mixed with copper salt and biomass polycarbon; Under an inert atmosphere, the powdered material is placed in a rotary kiln for sintering, so that the copper salt in the powdered material is decomposed and reduced by carbon to copper element, which is loaded into the biomass porous carbon to obtain the negative electrode material.
2. The preparation method according to claim 1, characterized in that: The copper salt includes one or more of copper sulfate, copper nitrate or basic copper chloride.
3. The preparation method according to claim 1, characterized in that: The mass ratio of copper ions to solvent in the copper precursor solution is 1:2000-1:
10.
4. The preparation method according to claim 1, characterized in that: The biomass porous carbon includes one or more of wood porous carbon, coconut shell porous carbon or straw porous carbon.
5. The preparation method according to claim 1, characterized in that: The air inlet temperature of the spray drying is 150° C.-250° C., the air outlet temperature is 110° C.-150° C., and the frequency is 150 Hz-280 Hz.
6. The preparation method according to claim 1, characterized in that: The sintering is specifically as follows: The temperature is raised from room temperature to 600°C-1000°C at a heating rate of 2°C / min-10°C / min, and kept at this temperature for 2 hours-10 hours.
7. The preparation method according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon.
8. A negative electrode material, characterized in that The negative electrode material is prepared by the preparation method described in any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode sheet comprises the negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Cited By
Preparation method of modified zinc-bromine flow battery carbon felt negative electrode and carbon felt negative electrode prepared by method
CN121237900A